DAMPAK OTONOMI DAERAH DAN PEMEKARAN WILAYAH TERHADAP PERKEMBANGAN KOPERASI DI INDONESIA - Siregar, Abi Pratiwa (Berkala Ilmiah AGRIDEVINA, 2019)
In 1999, the government issued Law No. 22 concerning Regional Autonomy. Then it followed  propose regional expansion, because they saw the opportunity to manage their own resources. From the point of view of co-operatives, the existence of regional autonomy and regional expansion are both opportunities and challenges. Opportunities came from the expectation that regional autonomy and regional expansion will bring a positive impact on co-operatives in terms of resource allocation. Meanwhile, the challenge is the activities and interventions of local government in co-operative activities. Because the principle of efficiency will urge cooperatives to build a broad network and possibly exceed the limits of the autonomous region. The purpose of this study is to determine the impact of regional autonomy and regional expansion on the development of co-operatives in Indonesia. The type of data used is secondary, originating from the Ministry of Cooperatives and SMEs. The analytical method used is simple linear regression (trend analysis). The results of the study show that since the enactment of regional autonomy followed by regional expansion, the trend of c-ooperative development has tended to be positive. If compared between the parent region and the newly created regions, the development of co-operatives in the parent region is relatively better. This is presumably because the newly created regions are still adapting to the administration and management of resources in the region.DOI : https://doi.org/10.33005/adv.v8i1.1602